Benextramine and derivatives as novel human monoamine oxidases inhibitors: an integrated approach. (29th July 2019) - Di Paolo, Maria Luisa; Cozza, Giorgio; Milelli, Andrea; Zonta, Francesca; Sarno, Stefania; Minniti, Elirosa; Ursini, Fulvio; Rosini, Michela; Minarini, Anna
Abstract : The two human monoamine oxidase isoforms (namely MAO A and MAO B) are enzymes involved in the catabolism of monoamines, including neurotransmitters, and for this reason are well‐known and attractive pharmacological targets in neuropsychiatric and neurodegenerative diseases, for which novel pharmacological approaches are necessary. Benextramine is a tetraamine disulfide mainly known as irreversible α‐adrenergic antagonist, but able to hit additional targets involved in neurodegeneration. As the molecular structures of monoamine oxidases contain nine cysteine residues, the aim of this study was to evaluate benextramine and eleven structurally related polyamine disulfides as potential MAO inhibitors. Most of the compounds were found to induce irreversible inactivation of MAOs with inactivation potency depending on both the polyamine structure and the enzyme isoform. The more effective compounds generally showed preference for MAO B. Structure‐activity relationships studies revealed the key role played by the disulfide core of these molecules in the inactivation mechanism. Docking experiments pointed to Cys323, in MAO A, and Cys172, in MAO B, as target of this type of inhibitors thus suggesting that their covalent binding inside the MAO active site sterically impedes the entrance of substrate towards the FAD cofactor. The effectiveness of benextramine in inactivating MAOs was demonstrated in SH‐SY5Y neuroblastoma cell line. These results demonstrated for the first time that benextramine and its derivatives can inactivate human MAOs exploiting a mechanism different from that of the classical MAO inhibitors and could be a starting point for the development of pharmacological tools in neurodegenerative diseases. Abstract : The polyamine disulfide benextramine and its analogues act as human monoamine oxidases (MAO) inhibitors, exploiting a novel inactivation mechanism. The disulfide core of compounds interacts covalently with the thiol group of Cys172 in MAO B isoform active site, leading to the formation of a new disulfide bond between the inhibitor and the enzyme. In this way, the entrance towards the FAD‐cofactor is hindered, resulting in enzyme inactivation.